2016
DOI: 10.1139/cjas-2015-0170
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of crude glycerin on ruminal parameters, microbial yield, and in vitro greenhouse gases production in dairy cows

Abstract: Holstein cows were used to evaluate the inclusion of elevated concentrations of crude glycerin on ruminal parameters, production of greenhouse gases, and microbial yield. The use of up to 300 g kg−1 reduces ruminal bacteria yield and NH3-N, without affecting the pH. Moreover, 300 g kg−1 glycerin increases methane production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
1
1
Order By: Relevance
“…The diets differed in pH end of incubation, however, not differ in the production of CH 4 and CO 2 produced in vitro (Table 1). This demonstrates that the inclusion of 10% glycerine in diet does not affect the production of CH 4 and CO 2 , contrary to the results of Van Cleef et al (2012) when evaluated in vitro production of greenhouse gases using different concentrations of crude glycerin (0; 7.5; 15; 22.5 and 30%) in cattle diets Nelore and noted that crude glycerine concentration independent decreased CH 4 and CO 2 , for 12 hours of incubation. Avila et al (2011) evaluating the in vitro production of diets containing up to 21% crude glycerine instead barley, found no effect on the generation of this gas.…”
Section: Resultscontrasting
confidence: 69%
“…The diets differed in pH end of incubation, however, not differ in the production of CH 4 and CO 2 produced in vitro (Table 1). This demonstrates that the inclusion of 10% glycerine in diet does not affect the production of CH 4 and CO 2 , contrary to the results of Van Cleef et al (2012) when evaluated in vitro production of greenhouse gases using different concentrations of crude glycerin (0; 7.5; 15; 22.5 and 30%) in cattle diets Nelore and noted that crude glycerine concentration independent decreased CH 4 and CO 2 , for 12 hours of incubation. Avila et al (2011) evaluating the in vitro production of diets containing up to 21% crude glycerine instead barley, found no effect on the generation of this gas.…”
Section: Resultscontrasting
confidence: 69%
“…Lo anterior dado a que podría generar alteraciones metabólicas, a partir de la fermentación en el rumen, modificando la síntesis de ácidos grasos de cadena corta, principalmente a propiónico y butírico. Es así, caso de la acidosis ruminal, en donde se produce en su mayoría ácido propiónico, modificando la sinergia ruminal con la reducción en la disponibilidad de ácido acético y butírico y presentando una disminución del pH (Rémond et al, 1993;Leão et al, 2012;Vinhas y Rondina, 2013;Van-Cleef et al, 2014;2016).…”
Section: Introductionunclassified
“…The glycerol (main constituent of crude glycerin) can be converted to glucose by the liver and kidneys to provide energy for cellular metabolism. In ruminants, the glycerol is fermented in the rumen into short chain fatty acids, mainly to propionic and butyric [ 6 ]. Recent studies have demonstrated that the inclusion of this by-product has effects on carcass grade [ 4 – 7 ], increases the intramuscular fat and oleic acid content [ 8 ], decreases myristic, palmitic and stearic acids in Longissimus muscle [ 9 ], increases the monounsaturated fatty acid (MUFA) content and conjugated linoleic acid content [ 10 ], decreases saturated fatty acid and increases unsaturated and odd-chain fatty acid contents [ 4 ].…”
Section: Introductionmentioning
confidence: 99%